Characterization of a transcriptional TPP riboswitch in the human pathogen Neisseria meningitidis. Issue 5 (3rd May 2020) - Righetti, Francesco; Materne, Solange Lise; Boss, John; Eichner, Hannes; Charpentier, Emmanuelle; Loh, Edmund
ABSTRACT: Increasing evidence has demonstrated that regulatory RNA elements such as riboswitches (RS) play a pivotal role in the fine-tuning of bacterial gene expression. In this study, we investigated and characterized a novel transcriptional thiamine pyrophosphate (TPP) RS in the obligate human pathogen N. meningitidis MC58 (serogroup B). This RS is located in the 5´ untranslated region upstream of thiC gene, encoding a protein involved in TPP biosynthesis, an essential cofactor for all living beings. Primer extension revealed the transcriptional start site of thiC . Northern blot analysis of thiC mRNA and reporter gene studies confirmed the presence of an active TPP-sensing RS. Expression patterns of the wild-type RS and site-specific mutants showed that it is an OFF switch that controls transcription elongation of thiC mRNA. Interestingly, the regulatory mechanism of the meningococcal thiC RS resembles the Gram-positive Bacillus subtilis thiC RS rather than the Gram-negative Escherichia coli thiC RS. Therefore, the meningococcal thiC RS represents a rare example of transcriptional RS in a Gram-negative bacterium. We further observed that the RS is actively involved in modulating gene expression in response to different growth media and to supplemented bacterial and eukaryotic cell lysates as possible sources of nutrients in the nasopharynx. Our results suggest that RS-mediated gene regulation could influence meningococcal fitness, through the fine-tuning of biosynthesis and scavenging of nutrients and cofactors, such as thiamine.